2023
DOI: 10.1177/03635465231188527
|View full text |Cite
|
Sign up to set email alerts
|

Medial Meniscus Posterior Root Repair Reduces but Does Not Avoid Histologic Progression of Osteoarthritis: Randomized In Vivo Experimental Study in a Rabbit Model

Lika Dzidzishvili,
Emilio Calvo,
Irene Isabel López-Torres

Abstract: Background: The optimal treatment option for meniscus root tears is still challenging, and whether the meniscus root repair ultimately can arrest or delay osteoarthritic changes is still a concern. Purpose/Hypothesis: The purpose of this study was 2-fold: (1) to describe and compare histopathologic findings of 3 different therapeutic options for medial meniscus posterior root tear: nonoperative management, partial meniscectomy, and meniscus root repair; and (2) to test the hypothesis that meniscus root tears t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 48 publications
0
1
0
Order By: Relevance
“…In light of our study's findings, the research conducted by Dzidzishvili et al provides compelling histopathologic insights into the treatment of meniscus root tears and its implications for osteoarthritic development, although in rabbit models, instead of humans [73]. The authors delineated the osteoarthritic changes across three experimental groups-partial meniscectomy, conservative treatment, and meniscus root repair-revealing that the repair group exhibited the least severe cartilage damage with a mean score of 2.5, compared to more pronounced OA signs in the meniscectomy group (mean score of 16) and the CT group (mean score of 5).…”
Section: Summary Of Evidencementioning
confidence: 51%
“…In light of our study's findings, the research conducted by Dzidzishvili et al provides compelling histopathologic insights into the treatment of meniscus root tears and its implications for osteoarthritic development, although in rabbit models, instead of humans [73]. The authors delineated the osteoarthritic changes across three experimental groups-partial meniscectomy, conservative treatment, and meniscus root repair-revealing that the repair group exhibited the least severe cartilage damage with a mean score of 2.5, compared to more pronounced OA signs in the meniscectomy group (mean score of 16) and the CT group (mean score of 5).…”
Section: Summary Of Evidencementioning
confidence: 51%
“…Regardless, MMPR repair does not completely prevent the progression of osteoarthritis and medial joint space (MJS) narrowing [2,8,14]. While many similar studies have reported on postoperative MM extrusion (MME) progression [19,23,29], a previous study reported that MMPR repair slowed the progression of osteoarthritis compared with conservative treatment or meniscectomy in a rabbit model [3]. Factors such as age, weight, quadriceps muscle strength, healing status of the repaired posterior roots and time from symptom onset to surgery have been reported to influence the progression of MJS, MME and osteoarthritis in the postoperative period after MMPR repair [7,11,24].…”
Section: Introductionmentioning
confidence: 99%